Prática e consciência das regras no jogo de Bola Queimada: contribuições para a educação física - Conti, Luana Cristine Franzini de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Physical Education has traditionally been conceived as a space for moral education, although this space has taken several connotations in the history of this discipline. The values propagated by it have changed according to the general changes in society. Currently, as we educate, we wish to encourage the construction of an autonomous morality. Thus, considering the theoretical framework adopted, the genetic epistemology and psychology, we found the need to first understand how moral judgments are built. In this sense, the present study aimed to investigate and analyze the relationships between the practice and the awareness of the rules in the children's game called bola queimada. In order to achieve this aim, an empirical research, of a qualitative character, was conducted. Interviews based on the Clinical Method were used as tools, with two types of script. The first addressed the reports about the practice of playing bola queimada, since the set of questions and answers made possible to assess how children used the rules of the game. The second script investigated the awareness of the rules, how they interpreted the mandatory nature of the same. The empirical research was conducted with children from four different age groups. Ten children from each age group, belonging to a public elementary school in the city of Londrina-PR, were interviewed. The hypothesis of our study indicates that there are links or relationships between the practice and the awareness of the rules; that the moral judgment is rooted in the practice, but is delayed in relation to it. The results from the issued reports on the practice were categorized according to the classification proposed by Piaget's theory: (1) motor rule; (2) egocentric rule; (3) nascent cooperation; (4) codification of rules. Our study encompassed only the last three stages and for each stage, indicator criteria were created in relation to the game studied. The reports on the...

A disciplina de Educação Física foi tradicionalmente concebida como espaço de formação moral, ainda que tal formação tenha assumido diversas conotações na história desta disciplina. Os valores por ela propagados mudaram de acordo com as transformações gerais da sociedade. Na atualidade, ao educar, desejamos favorecer a construção da moral autônoma. Sendo assim, diante do referencial teórico adotado, o da Epistemologia e Psicologia Genéticas, entendemos a necessidade de primeiramente compreender como se constroem os juízos morais. Neste sentido, o presente estudo teve como objetivo investigar e analisar as relações entre a prática e a consciência das regras no jogo infantil denominado de bola queimada. Para tanto, realizamos uma pesquisa empírica, de caráter qualitativo. Como instrumento utilizamos entrevistas baseadas no Método Clínico, com dois tipos de roteiro. O primeiro abordou os relatos acerca da prática do jogo de bola queimada, uma vez que o conjunto de indagações e respostas possibilitaram aferir como as crianças utilizavam as regras do jogo. O segundo roteiro investigou a consciência das regras, como elas interpretavam o caráter obrigatório das mesmas. A pesquisa empírica foi realizada com crianças pertencentes a quatro faixas etárias. Foram entrevistadas dez crianças por grupo, pertencentes a uma escola pública municipal do Ensino Fundamental I da cidade de Londrina-Pr. A hipótese de nosso trabalho indica que há vínculos ou relações entre a prática e a consciência das regras, que o juízo moral está enraizado na prática, mas se atrasa em relação à ela. Os resultados acerca dos relatos emitidos sobre a prática foram categorizados de acordo com a classificação proposta pela teoria piagetiana: (1) regra motora; (2) regra egocêntrica; (3) cooperação nascente; (4) codificação das regras, sendo que nosso estudo abarcou apenas os três últimos estágios. Para cada...
Keywords: Ensino fundamental; Educação fisica; Jogos; Ética; Physical education and training